The Role of Forensic Autopsy in Pursuit of Material Truth in Optical Evidence for Negative Legal Proof in the Cyanide Coffee Murder Case - Isnaeni, Belly (Sinergi International Journal of Law, 2024)
Conducting criminal investigations in Murder cases sometimes faces challenges in obtaining the family's consent for the victim's autopsy. This difficulty arises due to issues related to the victim's religious beliefs, which prohibit the autopsy of murder victims. The autopsy process by the investigative authorities encounters internal obstacles due to limited government funding for the autopsy process. The problem in this research is that, since no autopsy was conducted on Mirna's body, the cause of death remains unknown to establish material truth. The police can compel an autopsy based on Article 134, paragraph (1) of the Criminal Procedure Code, which includes the phrase "when it is highly necessary, and for the purpose of proving, a body autopsy cannot be avoided." Looking at this phrase, whether an autopsy is performed on murder victims is within the investigator's authority and based on the investigator's subjective considerations.